Relationship of Maternal Self-Efficacy in Exclusive Breastfeeding with Breastfeeding Frequency, Duration, and Child Nutritional Status - Megah Stefani; Maryam Zulfa Sabrin; Athiya Fadlina (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2024)
Breastfeeding self-efficacy denotes a mother's perceived confidence in her ability to breastfeed effectively. Elevated levels of maternal self-efficacy have been associated with increased breastfeeding frequency and improved breastfeeding performance, which positively impacts the child’s nutritional status, as exclusive breastfeeding is the optimal source of nutrition for infants aged 0-6 months. This research intended to analyze the association between maternal self-efficacy in exclusive breastfeeding and breastfeeding practices, including frequency and duration, as well as the nutritional status of children. This cross-sectional research was carried out between March and June 2024, involving 30 mothers of children aged 7-60 months who had been exclusively breastfed. Participants were selected through purposive sampling from families whose husbands were members of the AyahASI community. Data collection was carried out via Zoom meeting using the Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF) and WHO Anthro. Data analysis was conducted employing the Chi-square test and Pearson correlation coefficient. The results showed a significant relationship between maternal self-efficacy and breastfeeding duration (p=0.039; OR 10.11; CI 95% 1.05-97.00) and height-for-age z-score (HAZ) (p=0.042; r=0.374). However, no relationship was found with breastfeeding frequency (p=1.000), weight-for-age z-score (WAZ) (p=0.146), weight-for-height z-score (WHZ) (p=0.856), BMI-for-age z-score (BAZ) (p=0.588). This study indicate that a mother's self-efficacy in exclusive breastfeeding could be linked to a longer duration of breastfeeding and improved HAZ scores in children aged 7-60 months. However, due to the cross-sectional design, small sample size, and the non-random sampling method, these findings should be interpreted with caution and may not be generalizable to broader populations.